(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2025)
The genus Catumiri Guadanucci, 2004 includes five species from Argentina, Brazil, Chile and Uruguay. We describe courtship and copulation of Catumiri sp. from the Sierras de Balcarce, Argentina. Twelve units of sexual behavior (nine males/three females) were recorded. In addition, a new form of ootheca construction is reported.